A sample preparation method and device for polyacrylonitrile-based filament cross-section morphology

By using UV-curable adhesive for fixing and cutting, the problem of sample deformation in the cross-sectional morphology testing of polyacrylonitrile precursor fibers was solved, thus achieving accuracy and reliability of the test results.

CN122361047APending Publication Date: 2026-07-10FUJIAN ENERGY & PETROCHEMICAL INNOVATION RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610639802.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-07-10

AI Technical Summary

Technical Problem

In the sample preparation process, existing technologies can easily lead to inconsistent depths and deformation of the sample cross-section and the diameter of the precursor fiber during the testing of the cross-sectional morphology of polyacrylonitrile precursor fibers, affecting the accuracy and repeatability of the test results.

Method used

The polyacrylonitrile-based precursor fiber sample was fixed with UV-curable adhesive. After UV curing, the sample was cut from the solid slicer to avoid compression deformation of the sample during sample preparation. A release agent was used to remove the sample from the groove to ensure the integrity of the cross-sectional morphology.

Benefits of technology

This improves the accuracy and repeatability of polyacrylonitrile-based precursor fiber cross-sectional morphology detection, ensures the authenticity of sample cross-sectional morphology, and avoids detection errors caused by extrusion deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122361047A_ABST
    Figure CN122361047A_ABST
Patent Text Reader

Abstract

This invention relates to a method and apparatus for preparing samples of the cross-sectional morphology of polyacrylonitrile (PA) precursor fibers. The method comprises the following steps: taking a 50cm sample from the end of the PA precursor fiber to obtain a 10cm PA precursor fiber sample; fixing the PA precursor fiber sample onto a Y-shaped clamp in a stainless steel groove; slowly injecting UV-curable adhesive into the groove to uniformly immerse the PA precursor fiber sample in the adhesive; continuously irradiating the sample with a UV-curable flashlight for 5 seconds to cure it; after curing, using a release agent to remove the PA precursor fiber sample from the long groove; placing the cured PA precursor fiber sample into a solid slicer and cutting a 5mm section from the middle of the sample as the test sample. The sample preparation equipment for the cross-sectional morphology of PA precursor fibers in this invention is rationally designed, improving operational efficiency and saving time. It also avoids deviations from the true characterization caused by inconsistent sample cross-sectional depth and deformation of the precursor fiber diameter due to compression during sample preparation and cutting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a sample preparation method and apparatus, and more particularly to a sample preparation method and apparatus for the cross-sectional morphology of polyacrylonitrile-based precursor fibers. Background Technology

[0002] Carbon fiber is an advanced material with high strength, high modulus, and lightweight properties. Its core component is fiber with a carbon content of over 90%. Its superior performance makes it a revolutionary material in aerospace, defense, high-end sporting goods, new energy (wind power, pressure vessels), and automotive lightweighting.

[0003] Polyacrylonitrile precursor fibers are the precursors of high-performance carbon fibers. Their microstructure (such as cross-sectional shape, core-sheath structure, porosity, surface morphology, orientation, crystallinity, etc.) and macroscopic properties (such as strength, modulus, fineness uniformity, etc.) directly determine the quality of the final carbon fibers.

[0004] The diameter of polyacrylonitrile precursor fibers has a significant impact on the tensile strength of carbon fibers. The smaller the diameter of the polyacrylonitrile precursor fibers, the larger the surface area per unit volume of the precursor fibers. This is conducive to the occurrence of oxidation reactions during the pre-oxidation process and makes it easier to dissipate heat, resulting in better homogeneous carbon fibers. This, in turn, is beneficial for producing carbon fibers with better performance and higher tensile strength.

[0005] In existing methods for testing the cross-sectional morphology of polyacrylonitrile precursor fibers, the sample preparation process requires cutting the sample to observe its cross-sectional shape. However, this process is prone to inconsistencies in cross-sectional depth and deformation due to varying cutting forces or compression from the sample preparation equipment. The sample preparation equipment for the cross-sectional morphology of polyacrylonitrile precursor fibers in this invention is rationally designed, improving operational efficiency and saving time. Furthermore, it avoids deviations from the true characterization caused by inconsistent cross-sectional depth and deformation of the precursor fiber diameter during sample preparation and cutting.

[0006] Therefore, the sample preparation method of polyacrylonitrile precursor fibers is the prerequisite and foundation for successful characterization, and it directly affects the authenticity, accuracy and repeatability of the observation results. Summary of the Invention

[0007] To address the aforementioned technical problems, the present invention aims to provide a method and apparatus for preparing the cross-sectional morphology of polyacrylonitrile-based precursor fibers. This method avoids the problem of inconsistent depths and deformations in the cross-section of the test sample due to compression during sample preparation and cutting, which deviates from the true characterization and leads to inaccurate test results.

[0008] This invention discloses a method for preparing a sample with a cross-sectional morphology of polyacrylonitrile-based precursor fibers, characterized by the following steps:

[0009] (1) Take a sample from the end of the polyacrylonitrile precursor fiber, which is 50cm long, to obtain a polyacrylonitrile precursor fiber sample of about 10cm.

[0010] (2) Fix the polyacrylonitrile-based precursor fiber sample onto the Y-shaped clamp in the long groove;

[0011] (3) Slowly inject the UV-curable adhesive into the long groove so that the polyacrylonitrile-based precursor sample is evenly immersed in the UV-curable adhesive.

[0012] (4) Use a flashlight with ultraviolet light function to continuously irradiate the sample for 5 seconds to cure it;

[0013] (5) After the sample has cured, use a release agent to remove the polyacrylonitrile-based precursor sample from the long groove;

[0014] (6) Place the cured polyacrylonitrile-based precursor fiber sample into a solid slicer and cut a 5mm section from the middle of the sample as a test sample.

[0015] The present invention provides a sample preparation device for the cross-sectional morphology of polyacrylonitrile-based precursor fibers, characterized in that: the sample preparation device includes a profile with an elongated groove and Y-shaped clamps fixed at both ends of the elongated groove.

[0016] Preferably, the length, width and height of the above-mentioned elongated groove are 10*1*1cm, the thickness is not less than 0.5cm, and the material is stainless steel.

[0017] Preferably, the Y-shaped clip is composed of two elastic sheets, each of which includes a lower flat section and an upper bent section. The lower flat sections of the two elastic sheets are attached to each other and inserted into the slot at the end of the elongated groove. The upper bent sections of the two elastic sheets are arranged opposite each other to form a V-shaped opening.

[0018] Preferably, the UV curing agent in step (3) is a fast-curing adhesive.

[0019] Preferably, the ultraviolet curing agent is 1-hydroxy-cyclohexyl-phenyl ketone or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0020] Preferably, the release agent in step (5) is silicone oil, silicone resin or polyethylene glycol, which can effectively remove the cured sample from the elongated groove.

[0021] Preferably, the solid slicer in step (6) above includes a base plate and two cutting blades rotatably connected to the base plate. The base plate has a groove to avoid the two cutting blades, and a limiting block is fixed on the upper surface of the base plate to restrict the movement of the cured polyacrylonitrile-based precursor sample.

[0022] This invention uses UV-curable adhesive to immerse the sample flat in the adhesive. After the adhesive cures, the sample's morphology remains within the adhesive. After cutting with scissors, the sample's diameter is fully revealed. This solves the problem of inaccurate test results caused by the uneven depth of the polyacrylonitrile cross-section and deformation of the precursor fiber diameter due to sample compression during sample preparation. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a flowchart of the sample preparation process of the present invention;

[0025] Figure 2 , Figure 3 , Figure 4 , Figure 5 This is a schematic diagram of the structure of the elongated groove made of acrylic material according to the present invention;

[0026] Figure 6 , Figure 7 , Figure 8 , Figure 9 This is a schematic diagram of the solid slicer of the present invention;

[0027] Figure 10 The test results are for comparison (the cross-sectional depth of the comparative cut samples is different).

[0028] Figure 11 The results are for comparative tests (comparative cutting of samples and extrusion deformation).

[0029] Figure 12 The test results are for Example 1 (the cross-sections are on the same plane);

[0030] Figure 13 The test results are for Example 1 (the sample was not deformed by compression).

[0031] The central control reset foot pedal and its combined connection method of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Generally, unless otherwise specified, the components of the embodiments of the present invention described and shown in the accompanying drawings can be arranged and designed in various different configurations.

[0033] The method for preparing the cross-sectional morphology of polyacrylonitrile precursor fibers according to the present invention includes the following steps:

[0034] (1) Take a sample from the end of the polyacrylonitrile precursor fiber, which is 50cm long, to obtain a 10cm polyacrylonitrile precursor fiber sample;

[0035] (2) Fix the polyacrylonitrile-based precursor fiber sample onto the Y-shaped clamp of the elongated groove of the sample preparation device;

[0036] (3) Slowly inject the UV-curable adhesive into the long groove so that the polyacrylonitrile-based precursor sample is evenly immersed in the UV-curable adhesive.

[0037] (4) Use a flashlight with ultraviolet light function to continuously irradiate the sample for 5 seconds to cure it;

[0038] (5) After the sample has cured, use a release agent to remove the cured polyacrylonitrile-based precursor sample from the long groove.

[0039] (6) Place the cured polyacrylonitrile-based precursor sample into a solid slicer and cut a 5mm section from the middle of the sample as a test sample.

[0040] The above-mentioned sample preparation device includes a profile A1 with an elongated groove and a Y-shaped clamp A2 fixed on both ends of the elongated groove; the length, width and height of the elongated groove are 10*1*1cm, the thickness is not less than 0.5cm, and the material is stainless steel; the Y-shaped clamp is composed of two elastic plates, each of which includes a lower flat section and an upper bent section. The lower flat sections of the two elastic plates are attached to each other and inserted into the slot at the end of the elongated groove, and the upper bent sections of the two elastic plates are arranged opposite each other to form a V-shaped opening.

[0041] The UV-curable adhesive mentioned in step (3) is a fast-curing adhesive; the UV-curable adhesive can be 1-hydroxy-cyclohexyl-phenyl ketone or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0042] The release agent mentioned in step (5) is silicone oil, silicone resin or polyethylene glycol, which can effectively remove the cured sample from the long groove.

[0043] The solid slicer in step (6) includes a base plate A3 and two cutting blades A4 rotatably connected to the base plate. The base plate has a groove A5 to avoid the two cutting blades. A limiting block A6 is fixed on the upper surface of the base plate to restrict the movement of the cured polyacrylonitrile-based precursor sample.

[0044] Specific embodiments of the present invention are as follows:

[0045] Example 1: A 50cm sample was taken from the end of a polyacrylonitrile precursor fiber to obtain a 10cm polyacrylonitrile precursor fiber sample. The polyacrylonitrile precursor fiber sample was then fixed in a Y-shaped clamp within a stainless steel groove.

[0046] Slowly inject UV-curable adhesive into the groove to evenly immerse the polyacrylonitrile precursor sample in the UV-curable adhesive; continuously irradiate the sample with a UV-enabled flashlight for 5 seconds to cure it. After the sample has cured, use a release agent to remove the polyacrylonitrile precursor sample from the long groove. Place the cured polyacrylonitrile precursor sample in a solid slicer and cut out the middle 5mm portion of the sample as the test sample.

[0047] Comparative example: Take a bundle of polyacrylonitrile-based precursor fibers, wrap the polyacrylonitrile-based precursor fibers with a thin layer of degreased cotton, open the Y172 type Häss microtome, place the wrapped sample in the sample slot on the right bottom plate of the Y172 type Häss microtome, then use the left bottom plate of the Y172 type Häss microtome to squeeze the sample tightly in the sample slot, and use a double-sided stainless steel blade to cut out the test sample along the Y172 type Häss microtome.

[0048] Regarding the sample preparation method of Example 1, the test results show that the sample of Example 1 of this application exhibits the original morphology of polyacrylonitrile-based precursor fibers in the test results, and the sample end face is nearly circular. Figure 12 , Figure 13 .

[0049] Regarding the sample preparation method of the comparative example, the test results show that the comparative example sample of this application exhibits polyacrylonitrile-based precursor fibers in an extruded state, with polygonal end faces, as seen in the test results. Figure 10 , Figure 11 .

[0050] Based on the test results of Example 1 and the comparative example Figure 12 , Figure 13 and Figure 10 , Figure 11As can be seen, the end face of the polyacrylonitrile precursor fiber sample cut by the Y172 type Harley-Davidson microtome has residual inclusions, and the sample appears to be in a compressed state, with a polygonal shape. However, the polyacrylonitrile precursor fiber end face cut by the solid microtome after sample curing yields significantly better results, revealing the original morphology of the polyacrylonitrile precursor fiber, with a near-circular shape. This invention effectively avoids damage to the sample during sample preparation, thereby improving the accuracy of the polyacrylonitrile precursor fiber diameter test results.

[0051] The above embodiments are only used to illustrate the technical methods of this application, and are not intended to limit it. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A method for preparing a sample with a cross-sectional morphology of polyacrylonitrile-based precursor fiber, characterized in that: Includes the following steps: (1) Take a sample from the end of the polyacrylonitrile precursor fiber, which is 50cm long, to obtain a 10cm polyacrylonitrile precursor fiber sample; (2) Fix the polyacrylonitrile-based precursor fiber sample onto the Y-shaped clamp of the elongated groove of the sample preparation device; (3) Slowly inject the UV-curable adhesive into the long groove so that the polyacrylonitrile-based precursor sample is evenly immersed in the UV-curable adhesive. (4) Use a flashlight with ultraviolet light function to continuously irradiate the sample for 5 seconds to cure it; (5) After the sample has cured, use a release agent to remove the cured polyacrylonitrile-based precursor sample from the long groove. (6) Place the cured polyacrylonitrile-based precursor fiber sample into a solid slicer and cut a 5mm section from the middle of the sample as a test sample.

2. The method for preparing the cross-sectional morphology of polyacrylonitrile precursor fiber according to claim 1, characterized in that: The sample preparation device includes a profile with an elongated groove and Y-shaped clamps fixed at both ends of the elongated groove.

3. The method for preparing the cross-sectional morphology of polyacrylonitrile precursor fiber according to claim 1, characterized in that: The UV-curable adhesive mentioned in step (3) is a fast-curing adhesive.

4. The method for preparing the cross-sectional morphology of polyacrylonitrile precursor fiber according to claim 1, characterized in that: The UV-curable adhesive is 1-hydroxy-cyclohexyl-phenyl ketone or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

5. The method for preparing the cross-sectional morphology of polyacrylonitrile precursor fiber according to claim 1, characterized in that: The release agent in step (5) is silicone oil, silicone resin or polyethylene glycol, which can effectively remove the cured sample from the long groove.

6. The method for preparing the cross-sectional morphology of polyacrylonitrile precursor fiber according to claim 1, characterized in that: The solid slicer in step (6) includes a base plate and two cutting blades rotatably connected to the base plate. The base plate has a groove to avoid the two cutting blades, and a limiting block is fixed on the upper surface of the base plate to restrict the movement of the cured polyacrylonitrile-based precursor sample.

7. A sample preparation apparatus for implementing the sample preparation method according to any one of claims 1-6, characterized in that: The sample preparation device includes a profile with an elongated groove and Y-shaped clamps fixed at both ends of the elongated groove.

8. The sample preparation apparatus according to claim 7, characterized in that: The elongated groove has a length, width, and height of 10*1*1cm, a thickness of not less than 0.5cm, and is made of stainless steel.

9. The sample preparation apparatus according to claim 7, characterized in that: The Y-shaped clamp is composed of two elastic sheets, each of which includes a lower flat section and an upper bent section. The lower flat sections of the two elastic sheets are attached to each other and inserted into the slot at the end of the elongated groove. The upper bent sections of the two elastic sheets are arranged opposite each other to form a V-shaped opening.